Heading towards Internet Enhanced ESP Instruction - Radovanović, Aleksandra M.; Kraguljac, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The current study inquires into the Internet affordances and utility and focuses on its effective integration into English for Specific Purposes instruction at the Faculty of Hotel Management and Tourism. As no technological tool can of itself bring any improvements in learning, prior to its inclusion, the specific instruction context is to be investigated in order to make informed decisions in line with students' needs and interests and curricula objectives. For this reason, a survey on students' perceptions and attitudes was carried out. The findings enabled identifying the instructional aspects to be enhanced by the Internet and pointing out suggestions and remedial aspects. In general, the findings support the idea that the Internet maximum benefits can only be achieved through promoting two types of EFL language learning: overt and covert learning. Also, the overall integrative pedagogical approach is advocated.
Keywords: tourism; instruction; ESP; the Internet